2008
DOI: 10.1186/cc7006
|View full text |Cite
|
Sign up to set email alerts
|

Use of T2-weighted magnetic resonance imaging of the optic nerve sheath to detect raised intracranial pressure

Abstract: Introduction The dural sheath surrounding the optic nerve communicates with the subarachnoid space, and distends when intracranial pressure is elevated. Magnetic resonance imaging (MRI) is often performed in patients at risk for raised intracranial pressure (ICP) and can be used to measure precisely the diameter of optic nerve and its sheath. The objective of this study was to assess the relationship between optic nerve sheath diameter (ONSD), as measured using MRI, and ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
230
6
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(256 citation statements)
references
References 38 publications
15
230
6
5
Order By: Relevance
“…The ONSD was measured in an axis perpendicular to the optic nerve, 3 mm behind the globe. 6 The images were evaluated by two experienced radiologists. Agreement between the two radiologists was reached in consensus after careful individual evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…The ONSD was measured in an axis perpendicular to the optic nerve, 3 mm behind the globe. 6 The images were evaluated by two experienced radiologists. Agreement between the two radiologists was reached in consensus after careful individual evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…6,[17][18][19] Coronal image acquisition is optimal for visualizing the true dimensions of the ON and perioptic CSF relative to the surrounding sheath. 12 The most commonly reported macroscopic findings in MR images of patients diagnosed with papilledema are the following: 1) enlargement of the ONS, 5,6,8,9,20 2) flattening of the posterior sclera, [13][14][15] 3) protrusion of the optic papilla into the globe, 6,11 and 4) tortuosity of the ON.…”
Section: Mr Imaging Findingsmentioning
confidence: 99%
“…The association between increased intracranial pressure and increasing ONSD was also demonstrated in patients with traumatic brain injury. 10 A review of the literature has found very little regarding standardized norms of ONSD on MR imaging for adults, 11,12 and no established norms for children. The aim of this study was to establish age-correlated norms for pediatric ONSD and to compare the ONSD of a group of pediatric patients with IIH with a healthy control group.…”
mentioning
confidence: 99%